Natural polymeric biomaterials for tissue engineering - Pina, Sandra Cristina Almeida (2021)
Recent advances in tissue engineering (TE) have shown that combining biomaterials, cells, and bioactive molecules are important to promote the regeneration of damaged tissues or as therapeutic systems. Porous three-dimensional structures with interconnected pore network are capable to guide the development of functional engineered tissues and afford the temporary mechanical support during in vivo implantation. Natural polymeric biomaterials have been used for 3D scaffolds fabrication, owing its ability of mimicking the extracellular matrix, biocompatibility, biodegradability, and no immunological reactions, during tissue regeneration or wound healing. This chapter provides the most promising natural biopolymers - proteins, polysaccharides and marine origin polymers - their properties and considerations specifically for scaffolding TE purposes. The recent works related to micro- and nano-particles, 3D porous scaffolds and hydrogel-based scaffolds as biomimetic strategies for TE and regeneration are also presented and discussed herein.